Successes and Drawbacks of the Federal Reserve and the Impact on Financial Markets - RASHID, Muhammad Mustafa (Journal of Advanced Studies in Finance, 2019)
The purpose of this paper is to provide an outline of the successes and draw-backs of the Federal Reserve and the consequent impact on financial markets. A review of the relevant literature from Hubbard (2008) and Dowd and Hutchinson (2010) will provide insights into the success and failures of the Federal Reserve and the impact on financial markets. Further insights will be drawn from; Gorton and Metrick (2013) and their interpretation of the Federal Reserve’s actions since its formation, Romer and Romer (2013) on the pessimism of monetary policy and Dyugen-Bump ( et al. 2013) on their assessment of the effectiveness of emergency liquidity measures.